Peran Leadership Dalam Membentuk Karakter Santri di Ma’had Miftahul Jannah - Tri Suci Aryanti; Achmad Syarifudin (Social Science and Contemporary Issues Journal, 2024)
This research discusses "The Role of Leadership in Shaping the Character of Santri in Ma'had Miftahul Jannah District. Rambutan District. Banyuasin.” Leadership or leadership roles are a set of behaviors that are expected to be carried out by someone according to their position as a leader. The problems in this research are (1) What is the Role of Leadership in Shaping the Character of Santri in Ma`had Miftahul Jannah District. Rambutan District. Banyuasin?, (2) How to Measure the Success of the Leadership Role in Shaping the Character of Santri in Ma`had Miftahul Jannah District. Rambutan District. Banyuasin? This research aims to find out the role of leadership in shaping the character of students and how to measure the success of leaders in forming the character of students. The research method used is a qualitative research method, then the data collection tools used are observation, interviews and documentation. Data analysis is qualitative descriptive by means of data reduction, data presentation and conclusions. This research analyzes Henry Mintzberg's theory, namely personal role (interpersonal role), role of decision maker (decision role), role of information source (informational role). The results of this research show that the students' poor character is caused by environmental factors where they live and social interactions outside the ma'had. However, Ma'had's leadership or leadership has carried out its role as a leader well in forming the character of its students, resulting in the formation of good student character.